The Highlands and Their Inhabitants through the Eyes of 18th Century Englishmen: On Stereotypes in Intercultural Communication - Kosykh, T. A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
This article deals with the formation of the image of the Highlands in the English intellectual space of the 18th century. The research methodology is based on the concept of the image of the “Other”, implying a concrete historical analysis of different peoples’ collective ideas about each other. More particularly, the article focuses on the study of stable ethnic and cultural stereotypes as solidified images. Referring to Samuel Johnson’s A Journey to the Western Islands of Scotland (1775) the author describes the crucial English stereotypes about the inhabitants of the Highlands. Like many of his contemporaries, Dr. Johnson was convinced of the superiority of the English over the inhabitants of the Highlands. At the same time, his travel notes demonstrate his desire to scrupulously describe the life and customs of the Highlanders, show the peculiar features of mountaineers’ lifestyles, so different from those of Englishmen. The author comes to the conclusion about the predominance in English society of notions about the Highlands as an internal colony of Britain in need of being introduced to civilisation by means of Anglicisation. Dr. Johnson’s A Journey… is a valuable source for the study of stereotypes of English intellectual culture in the process of intercultural communication in Britain in the 18th century.